Analysis Impact of the Pruning Policy Budget Government to Volatility Composite Stock Price Index (IHSG): Approach Autoregressive Distributed Lag (ARDL), Vector Autoregression (VAR), and Granger Causality - Lusiana Sandra Oey; Yoyo Sudaryo; Nunung Ayu Sofiati; Andre Suryaningprang; Riyandi Nur Sumawidjaja (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
Contractionary fiscal policy through government budget cuts, as mandated by Presidential Instruction Number 1 of 2025 with a spending efficiency value of Rp306.69 trillion, has the potential to influence investor expectations and the stability of the Indonesian capital market. This study aims to analyze the effect of government budget cut policy implementation, proxied through state expenditure realization, on the volatility of the Indonesia Composite Stock Price Index (IHSG), in both the short run and the long run, and to examine the dynamic responses and causal direction alongside the policy interest rate, exchange rate, and the ASEAN regional stock index. The study uses monthly time-series secondary data from January 2018 to December 2025 (96 observations), analyzed using the Autoregressive Distributed Lag (ARDL) Bounds Test and Error Correction Model (ECM) for short-run and long-run relationships, the Vector Autoregression (VAR) model as the basis for Impulse Response Function (IRF) and Forecast Error Variance Decomposition (FEVD), and the Granger Causality Test to determine the direction of causality. The results show a significant long-run cointegrating relationship (Bounds Test F-statistic = 4.6428 > I(1) Bound at α=5%). State expenditure realization has a significant positive effect on IHSG volatility in the short run, but a negative effect significant at the 10% level in the long run, indicating a pattern in which short-run shocks reverse into a long-run stabilizing effect. The policy interest rate has a significant positive long-run effect, the exchange rate has a significant positive short-run effect, while the ASEAN regional index is not significant. An Error Correction Term of -0.5615 indicates an adjustment speed of 56.15% per month, and state expenditure realization is shown to be the largest external contributor (5.50%) to the variation in IHSG volatility and to have a unidirectional causal relationship with it.